Telecommunications Field Operations Supported by Augmented Reality a Systematic Review - Coleta, Giuliano; Cardoso, Alexandre; Lamounier, Edgard; Lima, Gerson (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
The main objective of this study has been to perform an extensive systematic review of publications related to augmented reality and how this technology can aid field operations for the telecommunications industry. The expected result is to validate the feasibility of a new proposed framework, which consists of an augmented reality application that makes use of mobile device sensors, such as GPS and compass, a database and computer vision, to provide relevant information to the user, who is in this case a technician working for a large telecommunications operator. The application will aid the technician’s tasks, since it provides some network equipment information, such as name, location and occupation rate.